Hermeneutika Hasan Hanafi dalam konteks penafsiran al-Qur’an - Mulyaden, Asep; Ridwan, Ahmad Hasan; Riyani, Irma (Hanifiya: Jurnal Studi Agama-Agama, 2022)
This study was conducted to try to understand Hasan Hanafi's hermeneutic thinking in the context of the interpretation of the Qur'an. Given that the Qur'an is a holy book that deserves to be applied throughout all times and in various places. There are various methods that can be used to interpret the Qur'an. One of them is the hermeneutic approach. Not a few hermeneutic figures who offer various concepts, from orientalists to Muslim scholars themselves. However, the interpretation of the Qur'an with hermeneutics that is relevant to the slogan above is an interpretation that can provide solutions to the problems of the people, especially Muslims. Among the theories that are appropriate and in line with these interests are the hermeneutics offered by Hanafi, namely the emancipatory critical hermeneutics. This model of hermeneutics is a science that determines the relationship between consciousness (critical attitude) and its object, namely the holy book. It has a lasting stage called the historical consciousness phase, the eiditic phase of consciousness, and the practical phase of consciousness. Hermeneutics is a science that can explain God's revelation from letters to reality, from logical to practical, from words to the world, and from God's thoughts into real life.